A comparative study of methods used to generate the arterial fiber structure in a clinically relevant numerical analysis. (20th March 2019) - Misiulis, Edgaras; Džiugys, Algis; Navakas, Robertas; Petkus, Vytautas
Abstract: The advanced constitutive material models of artery wall require the definition of the mean collagen fiber directions in the material configuration. There are several proposed methods; however, it is unclear how much does the fiber structures obtained by these methods differ one from the other and how much this difference may affect the results of the structural analysis of a clinically relevant scenario. Therefore, in this paper, we address this issue by presenting the results of the comparative study of our developed and currently state‐of‐the‐art fiber definition methods. In addition, we present the verification of our developed numerical model that incorporates the extended Holzapfel‐Gasser‐Ogden (HGO) constitutive material model and the generalized prestressing algorithm (GPA). In the case of the patient‐specific internal carotid artery (ICA), the percentage error of the mean fiber directions defined by different methods does not exceed 17.73% (at least 0.05%, at most 81.82%) and has negligible effect on the stress levels, as the percentage error of the mean circumferential Cauchy stress does not exceed 0.1%. Both fiber definition methods produce comparable fiber structure, but our proposed method has an advantage, as it does not depend on method and software used to model the arterial wall mechanics. Abstract : In the case of the patient‐specific internal carotid artery (ICA), the percentage error of the mean fiber directions defined by different methods does not exceed 17.73% (at least 0.05%, at most 81.82%) and has negligible effect on the stress levels, as the percentage error of the mean circumferential Cauchy stress does not exceed 0.1%. Our proposed fiber definition method has an advantage, as it does not depend on method and software used to model the arterial wall mechanics.